A right to exclusion or a right to migration? – Neither! - Tiedemann, Paul; Justus Liebig University Giessen (My University, 2023)
The discussion about the open-border postulate, initiated by Joseph H. Carens in 1983, is developing an ever-increasing dynamism in both Anglo-American and German-speaking philosophy. There are two positions in this discussion: (1) the view that states have the sovereign right to decide whether and under what conditions they grant entry and residence to aliens (the right to exclusion); (2) the view that all people have a moral right to global free movement (the right to migration). The essay defends the thesis that there is neither a moral right to migration nor a moral right to exclusion. In the relationship between states and aliens, the state of nature prevails. In the state of nature there are no moral rights and duties other than human rights. Neither the alleged right to migration, i.e. global free movement nor the alleged right to exclusion can be considered a human right. The study is focused solely on ethics. Positive law, which depends on many coincidences anyway, is not considered.
Keywords: ddc:340